Ação modulatória da proteína Anexina A1 sobre os efeitos do tratamento com Anti-TNF-α em modelo murino de colite experimental - Silva, Marina de Paula [UNIFESP] (2016)
The tumor necrosis factor-alpha (TNF-α) is a key cytokine in the triggering of the inflammatory bowel diseases (IBDs), constituting an interesting target to therapeutic strategies. However, anti-TNF-α drugs, such as the infliximab (IFX) can still promote side effects and non-responsiveness in some patients, bringing the need to investigate other mediators potentially related to the efficacy of this therapy. In the IBDs, the anti-inflammatory protein annexin A1 (AnxA1) has been associated to the protection of gastrointestinal mucosa. Here, we evaluated the role of the endogenous AnxA1 on the TNF-α blockage efficacy, in rodent model of colitis. To this end, we assessed the colitis induced by dextran sulphate sodium (DSS) in Balb/c mice. Mice deficient in AnxA1 (AnxA1-/-) were employed as an interesting tool to evaluate the relevance of this protein on the intestinal inflammatory condition, comparing with the wide type strain (WT). Mice were also treated with IFX after colitis induction. We consistently observed that the endogenous AnxA1 is related to the prevention of clinical and physiological manifestations on the experimental colitis treated with IFX, since no improvement was found in AnxA1-/- mice. On WT mice, the epithelial damages promoted by the DSS administration were prevented after treatment, which reduced the rectal bleeding and diarrhea, consequently. AnxA1 also preserves the colonic morphology after IFX by decreasing the histological score and protecting against collagen degradation. The interleukin-6 (IL-6) was increased during the colitis in WT and AnxA1-/- mice. The IFX treatment reduced this cytokine only in hte presence of AnxA1. The influx of neutrophils and TNF-? secretion were largely higher compared to WT. Phagocytes, which plays important pro-inflammatory roles, were more susceptible to apoptosis after IFX in the presence of AnxA1. The expression of endogenous AnxA1, was increased in the experimental colitis and decreased on treatment, showing that the inflammatory response is attenuated in this condition. We indicated, for the first time to our knowledge, that AnxA1 plays a critical role to the return of the intestinal homeostasis and constitute a potential biomarker of therapeutic efficacy.